(untitled) (Revista Escenarios Sociojurídicos, 2022)
The technological advances that have been generated in the different fields such as medicine, science, including the current changes in legal development, have given rise to an aura of insecurity in the exercise of the public function of administering justice, because the perceptible information that is exposed in the different technological platforms does not have real guarantees and limits that guarantee an adequate management of it within the judicial process. This article proposes the recognition of oblivion as an autonomous fundamental right, where its exercise and protection does not depend on the element of connectedness as a criterion for recognition. For this purpose, it is argued that the interpretation based on principles of the Constitutional Model entrenches the need to strengthen the right to be forgotten as a substratum of human prospective advancement not limited by historical occurrences that are planted in the repositories digital information. The relevance it has in the current technological era and especially in the implemented developments of so-called e-justice.